THE CITY OF NOVI SAD MUSEUM IN THE CULTURAL TOURIST OFFER - Mijuk, Nenad (The Business of Tourism, 2023)
Museum institutions occupy an important place in cultural and touristic movements. They represent objects of history, culture and heritage of a nation or area. They contain numerous valuable funds from the fields of archaeology, history, ethnology, architecture, fine and applied arts, as well as from the daily and everyday life of citizens. Novi Sad, the second largest city in Serbia, on the Pannonian plain, is known for its extremely rich history and cultural heritage. The museum complex named "Museum of the City of Novi Sad" was founded in 1954 and includes: the main or central building of the museum, the Collection of Foreign Art, the Memorial Collection of Jovan Jovanović Zmaj and the Meat Collection of Sremski Karlovac.The main goal of the work is to present the tourist offer of the Museum, and to determine its positive and negative cultural-historical values ​​through tourism valorization using the qualitative-quantitative method and SWOT analysis, and thus to point out the potential that this institution can have in the development of tourism. Novi Sad and the whole country.
Keywords: Museum; Novi Sad; culture; tourism